Resolving asymmetries along the pulsation cycle of the Mira star X Hydrae - Haubois, Xavier; Wittkowski, M.; Perrin, G.; Kervella, P.; Mérand, A.; Thiébaut, E.; Ridgway, S. T.; Ireland, M.; Scholz, Michael (Astronomy and astrophysics, 2015)
Context. The mass-loss process in Mira stars probably occurs in an asymmetric way where dust can form in inhomogeneous circumstellar molecular clumps. Following asymmetries along the pulsation cycle can give us clues about these mass-loss processes.Aims. We imaged the Mira star X Hya and its environnement at different epochs to follow the evolution of the morphology in the continuum and in the molecular bands.Methods. We observed X Hya with AMBER in J-H-K at low resolution at two epochs. We modelled squared visibilities with geometrical and physical models. We also present imaging reconstruction results obtained with MiRA and based on the physical a priori images.Results. We report on the angular scale change of X Hya between the two epochs. 1D CODEX profiles allowed us to understand and model the spectral variation of squared visibilities and constrain the stellar parameters. Reconstructed model-dependent images enabled us to reproduce closure phase signals and the azimuthal dependence of squared visibilities. They show evidence for material inhomogeneities located in the immediate environment of the star.